Arginine vasopressin secretion in Kenyan children with severe malaria. - Sowunmi, A; Newton, C; Waruiru, C; Lightman, S; Dunger, D (2000)
Hyponatraemia is common in African children with severe malaria, but the cause is unknown. We measured plasma sodium (p[Na]) and arginine vasopressin concentrations (p[AVP]) in 30 consecutive children with severe malaria (19 had cerebral malaria), on admission, at 48 and 96 h after admission. Hyponatraemia (p[Na] < 130 mmol/l) occurred in 53 per cent of the children and was unrelated to peripheral parasite density, dehydration or abnormal renal function. The highest p[AVP] were seen in patients with cerebral malaria. Overall, p[AVP] declined 96 h after treatment. In children with hyponatraemia (cerebral and non-cerebral), p[AVP] levels were not suppressed and in 67 per cent of cases they were deemed inappropriate. Inappropriate AVP secretion is common in children with severe malaria and may influence fluid therapy after correction of initial dehydration.